Engaging a family's support network in non‐violent resistance: the experiences of supporters. Issue 2 (22nd March 2019) - Hicks, Stephanie; Jakob, Peter; Kustner, Claudia
Abstract : Non‐violent resistance (NVR) is a systemic approach which aims to build parent agency and a positive support network around children who display destructive behaviour. Supporters play a key role in NVR, but there is limited research on how to engage them in NVR. The aim of this study was to explore the experiences of the members of a family's support network on the implementation of NVR. These experiences were then interpreted in line with theories of motivation and change in order to understand how the NVR practitioner and parents can best engage with supporters in future. Eight supporters were interviewed and themes developed using interpretative phenomenological analysis. The study analysis found five themes: contemplation, committing to action, looking for change, needing to cope and working within a social context. These are interpreted in line with theories of change and motivation. Clinical recommendations and recommendations for further research are discussed. Practitioner points: Practitioners need to consider that taking part in NVR can be experienced by supporters in both positive and negative ways Practitioners may improve supporters' engagement and motivation in the process by considering areas such as understanding NVR, positive communication and impact on relationships 让家庭支持网络参与非暴力抵抗：支持者的经历: 非暴力抵抗（NVR）是一种系统性方法，旨在建立家长能动性以及围绕表现出破坏性行为的儿童的积极支持网络。支持者在NVR中发挥着关键作用，但关于如何让他们参与NVR的研究却很有限。本研究的目的是探讨家庭支持网络成员在实施NVR方面的经历。研究者通过动机和变化理论对这些经历进行解释，以了解NVR从业者和家长将来如何以最佳的方式与支持者互动。我们采访了八位支持者，并用阐释现象学分析生成了主题。研究分析发现了五个主题：沉思，决心行动，寻找变化，需要应对和在社会情境中工作。这些都根据变化和动机理论进行了解释。本文还讨论了临床以及进一步研究的建议。 对实务工作者的启示: 实务工作者需要认识到支持者参与NVR的经历可以是积极的，也可以是消极的 实务工作者可以通过考虑理解NVR，积极沟通和对关系的影响等方面来提高支持者在此过程中的参与度和积极性 Involucrar a la red de apoyo de una familia en la resistencia no violenta: las experiencias de las personas de apoyo: La resistencia no violenta (NVR, por sus siglas en inglés) es un enfoque sistémico que apunta a construir eficacia en padres y una red de apoyo positiva alrededor de niños que muestran un comportamiento destructivo. Las personas de la red de apoyo desempeñan un papel clave en la NVR, pero existe poca investigación sobre cómo involucrarlos en la NVR. El objetivo de este estudio fue explorar las experiencias de los miembros de una red de apoyo familiar en la implementación de la NVR. Estas experiencias se interpretaron de acuerdo con las teorías sobre motivación y cambio para comprender cómo el profesional y los padres de NVR pueden participar mejor con los miembros de la red de apoyo en el futuro. Ocho personas de red de apoyo fueron entrevistados y los temas analizados utilizando el método fenomenológico interpretativo. El análisis del estudio encontró cinco temas: contemplación, compromiso con la acción, búsqueda de cambios, necesidad de afrontamiento y trabajar dentro de un contexto social. Estos temas se interpretan de acuerdo con las teorías del cambio y la motivación. Se discuten las recomendaciones clínicas y recomendaciones para futuras investigaciones. Puntos de implicación práctica: Los profesionales deben considerar que las personas de la red de apoyo pueden experimentar la participación en la NVR de manera positiva y negativa Los profesionales pueden mejorar el compromiso y la motivación de las personas de la red de apoyo en el proceso al considerar áreas como la comprensión de la NVR, la comunicación positiva y el impacto en las relaciones